La experiencia del patrimonio arquitectónico maya y su influencia en la Arquitectura - Mansur Garda, Juan Carlos (Restauro Compás y Canto S.A., 2021)
This article seeks to raise awareness about the value of preserving the pre-Hispanic Mayan heritage for the development of art, for which it accounts for the influence that pre-Hispanic art had in the nineteenth and twentieth centuries at a national and international level and reflects on how the experience and the language of pre-Hispanic Mayan architecture influenced international architects such as Frank Lloyd Wright and Jorn Utzon.